Purification of Bacterial Endotoxins by Zonal Centrifugation - Mendiola, L. R. (1972)
In this paper, we describe a cultivation procedure in large-capacity fermentors (200 liters) and the purification of the Salmonella crude extracts by means of zonal centrifugation in a sucrose gradient. Briefly, the endotoxin has been extracted from salmonellae with hypertonic solutions. The crude endotoxin was shown to contain several antigens, mainly r(1), r(2), r(3), or heterologous antigen. The heavy endotoxin was isolated and purified previously by enzymatic digestion, followed by a series of gel filtrations on Sephadex or Sepharose columns. We report the isolation and purification of heavy endotoxin in sucrose gradients, with the use of a B XIV titanium zonal rotor. From 150 to 300 mg of the crude material resuspended in a solution containing 1 m sodium chloride, 0.1 m sodium citrate, and 2.5% (w/w) sucrose, has been submitted to zonal centrifugation in gradients consisting of 5 to 25% (w/w) sucrose, also containing 1 m sodium chloride and 0.1 m sodium citrate. An overlay of 200 ml of 1 m sodium chloride-0.1 m sodium citrate was introduced after the sample. The separations were obtained after centrifugation for 3.5 hr at 35,000 rev/min (∫w(2)dt = 1.66 × 10(11)) at 4 C; the heavy endotoxin sedimented as heterogeneous material, from the middle toward the distal portions of the gradient. The heterologous antigens (r(1), r(2), r(3)), as well as bacterial proteins, remained in the sample zone. The heavy endotoxin recovered from the gradients was quite pure, as revealed by immunodiffusion tests against several antibacterial sera.